Construction of steady-active self-supported porous Ir-based electrocatalysts for the oxygen evolution reaction - Wang, Yongsheng; Guo, Xiaoxuan; Wang, Xinyu; Huang, Junling; Yin, Likun; Zhu, Wei; Zhuang, Zhongbin (Chemical communications (Cambridge, England), 2023)
Developing highly active and stable oxygen evolution reaction (OER) catalysts for water electrolysis remains a great challenge. A self-supported Ir nanocatalyst was prepared via a self-assembly method. Its porous structure and residual metal incorporation contributed to its high activity and stability for the OER in acid. A self-supported Ir nanocatalyst was prepared via a facile self-assembly method. The porous structure and residual metal incorporation contributed to the high activity and stability of the nanocatalyst for the oxygen evolution reaction in acid.